Boosting Psychological Well-being in One Session: A Rapid Counseling Approach to Digital Detox and Music Therapy - Oentarto, Aryobimo (citeus, 2026)
The rapid acceleration of technology has trapped modern youth in a digital connectivity paradox, where constant social media exposure triggers cognitive distortions and maladaptive behaviors that erode psychological well-being. This study evaluates the effectiveness of a Rapid Counseling approach integrated with Single-Session Music Therapy (RC-SSMT) in enhancing the psychological well-being of youth by breaking the cycle of digital addiction. Using a pre-test and post-test experimental design, the study focused on six youths (aged 15–17) at Church